Genotoxic and cytotoxic effects of thiomersal and paracetamol combination - Klepo, Dženana; Maleškić Kapo, Sanita; Mačkić-Đurović, Mirela; Aganović-Mušinović, Izeta; Burnazović-Ristić, Lejla (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Thiomersal is used as a preservative of some vaccines or as a trace from the pathogen inactivation process in vaccine production. Prophylactic use of paracetamol upon vaccination is still common, even though paracetamol decreases immune response on some vaccines. Considering the cytotoxic and genotoxic potential of thiomersal and paracetamol and possible interaction in vivo, in vitro study was performed. Methods: The genotoxic and cytotoxic effects of thiomersal and paracetamol combination were examined on human lymphocyte cultures by using two methods: analysis of chromosomal aberrations and cytokinesis-block micronucleus cytome assay. Blood samples of three healthy donors were analyzed with the following concentrations of tested substances: thiomersal 1 µg/ml and 0.5 µg/ml, paracetamol 20 µg/ml, thiomersal 0.5 µg/ml with paracetamol 20 µg/ml and thiomersal 1.0 µg/ml with paracetamol 20 µg/ml. Results: The analysis of structural chromosomal aberrations was significantly increased in all treated cultures. In cells treated with the combination of thiomersal 1 µg/ml and 20 µg/ml of paracetamol, the number of aberrations was significantly decreased. Cytokinesis-block micronucleus cytome assay analyses showed significantly increased micronucleus frequency in lymphocytes cultivated with thiomersal 1 µg/ml compared to lymphocytes cultures exposed to thiomersal 0.5 µg/ml. Conclusions: Induction of structural chromosome aberrations and micronucleus is shown as a sign of genotoxicity for the examined concentrations of thiomersal and paracetamol. The suppressing effect of paracetamol on thiomersal genotoxicity in lymphocytes culture treated with thiomersal was shown to be indicative of further examination of paracetamol use in the prevention of genotoxicity.